ANALISIS KESULITAN MEMBACA PERMULAAN SISWA KELAS 1 SDN PUCANGREJO KABUPATEN KENDAL - Aulia Munalifa; Mudzanatun; Ariestika Damayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this research is that the researcher once carried out the campus teaching program at SDN Pucangrejo, Kendal Regency. The researcher observed that the reading ability of students at SDN Pucangrejo, Kendal Regency was relatively low. Even some children who had already reached higher grades were still unable to read. This condition became the reason for the researcher to study reading difficulties, starting from the lower grades, because early reading is the foundation for further learning. It is expected that students will later be able to understand the subject matter more easily in the next grade. The focus of this study is the initial reading difficulties experienced by first-grade students of SDN Pucangrejo, Kendal Regency, with the purpose of analyzing various obstacles in early reading faced by these students. The type of research used is qualitative research, with research subjects consisting of first-grade students of SDN Pucangrejo, the first-grade teacher, and the school principal. Data collection techniques include observation, reading tests, peer questionnaires, and interviews. The results of the data analysis described indicate that the early reading difficulties among first-grade students of SDN Pucangrejo include inability to recognize letters, inability to read syllables or words, inability to read words correctly, inability to arrange letters into words, and inability to understand the meaning of the text. Based on these findings, the suggestions that can be given are: teachers are expected to provide more specific attention to students who are still unable to read, and students should develop the habit of practicing reading at home.